The Values of Synthetic Biology: Researcher Views of Their Field and Participation in Public Engagement. (8th August 2018) - Rose, Kathleen M; Howell, Emily L; Scheufele, Dietram A; Brossard, Dominique; Xenos, Michael A
Abstract: The synthetic biology research community will influence the future development of synthetic biology and its emergence into the sociopolitical and regulatory arenas. Because of this influence, we provide a first look at those involved in the research field—their views regarding the field and interactions with the public—using a unique sample of United States–based researchers who have published in the broad field of synthetic biology. Our data indicate a range of views of the moral and regulatory aspects of the science, based in part on various values and professional judgments, with differences emerging across synthetic biologists (e.g., bench scientists and computer scientists) and researchers focusing on ethical, legal, and social implications (ELSI). Importantly, the researchers are engaged in public outreach activities, which could provide opportunities for public discourse on the sociopolitical aspects of synthetic biology. The implications of these findings for the future of the technology and upstream engagement emerge.